2011
DOI: 10.1021/jf103532x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Konjac Glucomannan on Putative Risk Factors for Colon Carcinogenesis in Rats Fed a High-Fat Diet

Abstract: The aim of this study was to determine effects of konjac glucomannan (KGM) in a high fat corn oil diet on risk factors of colon carcinogenesis, that is, fecal β-glucuronidase, mucinase, and bile acids, and on preventive factors, that is, fecal microflora and cecal short-chain fatty acids (SCFAs). Sprague-Dawley rats (n = 8 animals per group) were fed a normal-fat fiber-free (5% corn oil, w/w) or high-fat (25% corn oil, w/w) diet containing no fiber, KGM (5%, w/w), or inulin (5%, w/w, as a prebiotic control) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…When used in food and ingested in the human digestive tract, KGM contributes to healthier digestion and the excretion of solid waste (Arvill & Bodin, 1995; Kaats, Bagchi & Preuss, 2015). Studies have also shown that KGM and some alkaloids in Amorphophallus have inhibitory effects on many diseases (Doi et al, 1979; Fan et al, 2008; Wu & Chen, 2011). Current transcriptome data for Amorphophallus have been deposited in the NCBI database, and these data accelerate the progress of studies on the important genes and in the molecular breeding of this species (Gille et al, 2011; Zheng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…When used in food and ingested in the human digestive tract, KGM contributes to healthier digestion and the excretion of solid waste (Arvill & Bodin, 1995; Kaats, Bagchi & Preuss, 2015). Studies have also shown that KGM and some alkaloids in Amorphophallus have inhibitory effects on many diseases (Doi et al, 1979; Fan et al, 2008; Wu & Chen, 2011). Current transcriptome data for Amorphophallus have been deposited in the NCBI database, and these data accelerate the progress of studies on the important genes and in the molecular breeding of this species (Gille et al, 2011; Zheng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The SCFA butyrate, produced as a bacterial by-product of inulin fermentation, has been shown to increase colonic glutathione production [104]. Glutathione is an antioxidant co-factor required for glyoxalase I activity, an enzyme which degrades the AGE precursor methylglyoxyl.…”
Section: Discussionmentioning
confidence: 99%
“…14) These acids, which are highly cytotoxic intestinal microbial metabolites of primary bile acid, promote colon cancer development. 15,16) A high-fat (HF) diet increases fecal secondary bile acids and decreases cecal organic acid production, 17) and is believed to increase the risk of colon cancer and of ulcerative colitis. 18,19) Our recent studies provide evidence of the favorable effects of certain polyphenols, which reduce secondary bile acids such as lithocholic acid and deoxycholic acid.…”
mentioning
confidence: 99%